Tradern console table from neolamarckia cadamba / 'Ainul Farhani Abdul Fatta - Abdul Fatta, 'Ainul Farhani (Faculty of Applied Sciences, 2017)
The purpose of the study is to design and produce a Tradern console table from Neolamarckia cadamba. This is to create a new design of console table by using Neolamarckia cadamba with a combination of traditional and modern style. The new design is only aimed at consumers living in terrace and apartment houses. This study has been proven that tradern console table that combines traditional and modern style can be successfully proceed. 100 correspondents a questionnaire and results showed that they believe this product can be commercialized and sold in the market. As the majority of correspondents had given positive feedback, it can be assumed that the tradern console table which combines traditional and modern style has successfully been aligned with the latest trend.